Single-cell RNA sequencing reveals the immune microenvironment and signaling networks in cystitis glandularis - Zhou, Tai Lai; Chen, Heng Xin; Wang, Yin Zhao; Wen, Si Jie; Dao, Ping Hong; Wang, Yu Hang; Chen, Min Feng (Frontiers in Immunology, 2023)
Cystitis glandularis (CG) is a common chronic bladder hyperplastic disease. The current lack of unified diagnosis and treatment criteria makes it essential to comprehensively describe the inflammatory immune environment in CG research. Here, we performed scRNA-sequencing in CG patients for the first time, in which four inflamed tissues as well as three surrounding normal bladder mucosa tissues were included. Specifically, we isolated 18,869 cells to conduct bioinformatic analysis and performed immunofluorescence experiments. Our genetic results demonstrate that CG does not have the classic chromosomal variation observed in bladder tumors, reveal the specific effects of TNF in KRT15 epithelial cells, and identify a new population of PIGR epithelial cells with high immunogenicity. In addition, we confirmed the activation difference of various kinds of T cells during chronic bladder inflammation and discovered a new group of CD27-Switch memory B cells expressing a variety of immunoglobulins. Our study reveals, for the first time, the different kinds of cell subgroups in CG and provides the necessary basis for the clinical treatment of cystitis glandularis.